Zebrafish etv7 regulates red blood cell development through the cholesterol synthesis pathway - Anita M. Quintana; Fabrizio Picchione; Ramon I. Klein Geltink; Michael R. Taylor; Gerard C. Grosveld (The Company of Biologists, 2014)
ETV7 is a human oncoprotein that cooperates with Eμ-MYC to promote pre-B-cell leukemia in mice. It is normally expressed in the bone marrow and fetal liver and is upregulated in primary leukemia, suggesting that it is involved in proper hematopoiesis and leukemogenesis. ETV7 has been deleted in most rodents, but is conserved in all other vertebrates, including the zebrafish, Danio rerio. In this report, we characterize the function of the zebrafish etv7 gene during erythropoiesis. Our results demonstrate that etv7 regulates the expression of the zebrafish lanosterol synthase (lss) gene, an essential gene in the cholesterol synthesis pathway. Furthermore, morpholino knockdown of etv7 leads to loss of hemoglobin-containing red blood cells, a phenotype that can be rescued by injection of exogenous cholesterol. We conclude that etv7 is essential for normal red blood cell development through regulation of the lss gene and the cholesterol synthesis pathway.